2018
DOI: 10.4103/jfo.jfds_55_16
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of correlation between dental calcification stages and skeletal maturity indicators

Abstract: Introduction: Assessment of age is a critical step in the identification of an individual in forensic cases. The hand–wrist radiographic evaluation and tooth development is also a useful measure of maturity because it represents a series of recognizable changes that occur in the same sequence from an initial event to a constant end point. Aim of the Study: To investigate the relationship of dental calcification stages and skeletal maturity indicators as assessed by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 14 publications
1
14
0
3
Order By: Relevance
“…A maturação dentária de acordo com Demirjian et al [11] não apresentou uma boa correlação com o método de avaliação da maturação mão-punho. Tal fato difere de alguns estudos que propõem que a maturação dentária possa ser usada como critério diagnóstico para avaliação do surto puberal [19,25,27]. Os resultados do presente estudo advêm de número amostral reduzido em relação aos demais.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…A maturação dentária de acordo com Demirjian et al [11] não apresentou uma boa correlação com o método de avaliação da maturação mão-punho. Tal fato difere de alguns estudos que propõem que a maturação dentária possa ser usada como critério diagnóstico para avaliação do surto puberal [19,25,27]. Os resultados do presente estudo advêm de número amostral reduzido em relação aos demais.…”
Section: Discussionunclassified
“…As meninas apresentam um desenvolvimento puberal mais precoce em relação ao sexo masculino e parecem atingir a maturação dentária também um pouco mais cedo [18], entretanto, na avaliação estratificada pelo sexo, ambos os sexos tiveram uma correlação apenas moderada entre os métodos esqueléticos e dentários. Além disso, uma ampla faixa etária também pode afetar os resultados da correlação, pois os métodos de maturação esquelética são incapazes de detectar as alterações com precisão [27].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Previous publications determined the degree of correlation between dental calcification and skeletal maturation finding diverse values [22][23][24][25][26]. Uysal et al [8] in Turkish subjects indicated that the lower second molar showed the greatest correlation (r � 0.82 in women and r � 0.70 in men), while the lower third molar showed the lowest correlation (r � 0.49 in women and r � 0.41 in men).…”
Section: Discussionmentioning
confidence: 99%
“…The dental literature has no scarcity for research related to correlation between dental calcification stages and skeletal maturation stages. But these studies have the following shortcomings: (a) lack of sample size calculation [ 14 21 ], (b) very small sample size [ 17 ], (c) evaluation of maxillary teeth while they are superimposed by other structures [ 22 ], (d) wide age range (patient age greater than 16 years) [ 19 , 20 ], and (e) inclusion of teeth at the age where root formation either has not yet started or has already been completed [ 14 , 18 20 ]. A systematic review and meta-analysis [ 23 ] also pointed out methodology errors and high heterogeneity in the published on this topic research.…”
Section: Introductionmentioning
confidence: 99%